PERCERAIAN DINI: STUDI TERHADAP PUTUSAN PENGADILAN AGAMA PEKALONGAN TAHUN 2013 - Ahmad Tugabus Surur; Hanik Rosyidah (Jurnal Hukum Islam, 2016)
This research aims to investigate the current phenomenon of divorce by young spouses who have short marriage, to discover the underlying factors causing early divorce, and to know how the judge resolves the case of early divorce. The word "early" in the title refers to the spouses who have short marriage, In fact, the inability of the spouses to face the reality of life made them difficult to adjust the various problems in the young age marriage. They have been sued each other to divorce even they have less than one year of marriage. They should reconsider their decision to divorce. This case can be seen in the Religious Court of Pekalongan. There were 24 cases of divorce in the young age of marriage in Religious Court in Pekalongan in 2013.